Green Economy as a Balancing Tool Between Humans and Nature in Various Asian Countries - Prasetia, Agung; ferreira, Paulino da costa (Business and Investment Review, 2024)
A green economy is a step in improving the economy that connects us with the natural world around us. In this case, the green economy seeks to build an economy in order to equalize society's economy, not only from a financial perspective but also from an environmental perspective because we are in contact with the environment every day. For this reason, the role of society is very influential in improving environmental and social welfare, one of which can be implemented in society is improving the education of their children. One important aspect of a green economy strategy is overcoming future problems. In particular, the green economy emphasizes determining the prices of goods and services that come from nature, whether plants, animals, or ecosystems. The green economy also identifies every function in nature that is useful for generating income for society. In this article, we use qualitative methods which we have used because the source of the information we obtain is based on case studies. Itself means data obtained through more detailed observations from the source person. From all the journals we took, we explained the concept and challenges of a green economy in sustainability in society with a focus on environmental growth and community welfare.